2019
DOI: 10.20473/jn.v14i1.15056
|View full text |Cite
|
Sign up to set email alerts
|

Leader Empowering Behaviors and Psychological Empowerment as Perceived by Young Hospital Staff Nurses: A Pilot Study

Abstract: Introduction: Empowerment has become an important concept in nursing that has gained acknowledgment in theories and practice of leadership and management. A positive organization espouses empowerment to attract and retain employees. While it is not new to nursing, there is little published research on empowerment among nurses in the Philippines. This study aimed to measure young staff nurses’ perception of leader empowering behaviors and psychological empowerment.Methods: This study used a cross-sectional surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…65 One of the essential functions of nursing leadership is staff empowerment to create a productive workplace culture for quality and safe care. 68 Our results showed that nurses' perceptions of their managers as ethical leaders increases the PE and dimensions of "impact", meaning, and trust. These results are consistent with the findings of other studies.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…65 One of the essential functions of nursing leadership is staff empowerment to create a productive workplace culture for quality and safe care. 68 Our results showed that nurses' perceptions of their managers as ethical leaders increases the PE and dimensions of "impact", meaning, and trust. These results are consistent with the findings of other studies.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, the results indicated that nurses' CB was at a desirable level which are congruent with previous studies. 59–63 Nurses' actions and competencies are considered as moral virtues and modulators of CBs, although there are challenges in practice. Similar to other studies, 3 most nurses emphasized technical activities of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LEB is a dynamic process that allows leaders or supervisors to delegate responsibility, authority, and autonomy toward their employees to enhance their self-control and self-management [ 10 ]. LEB mainly involves the cultivation of personal skills, the encouragement of innovation, and the sharing of information among staff nurses [ 11 ]. LEB among nurses reduces burnout levels and turnover intention [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to develop UCNs' knowledge, attitudes, beliefs, practices, and perceptions about patient safety. In the literature, it is emphasized that UCNs influence the nurses they work with through the transfer of knowledge, skills, and behaviors (6) and the UCNs who are empowered on a particular subject also empower the nurses with whom they work (7). Staff nurses, who provide the closest level of healthcare services to patients 24 hours a day, seven days a week, account for the largest workforce in health care institutions and are thus, an essential workforce in changing or reestablishing PSC.…”
Section: Introductionmentioning
confidence: 99%